Effect of electron beam irradiation on differently treated carbon fiber-filled acrylonitrile butadiene styrene for EMI shielding - Abbasi, Muhammad Inam; Alkaseh, Adel M. Ali; Abd Manaf, Mohd Edeerozey; Shueb, Mohammed Iqbal; Shamsudin, Zurina; Taha, Bilal Salman; Zeain, Mohammed Yousif; Wong, Adam Yoon Khang (The Electromagnetics Academy, 2025)
The burgeoning reliance on electronic devices in sectors such as aerospace systems and consumer electronics necessitates robust electromagnetic interference (EMI) shielding. Current challenges often involve balancing material performance with sustainability and cost-effectiveness. This study addresses these needs by exploring the use of recycled carbon fiber (rCF) in acrylonitrile butadiene styrene (ABS) composites for enhanced EMI shielding, contributing to more sustainable material development. We investigated the impact of different rCF treatments (untreated, chemically treated, and chemically-mechanically treated) on mechanical properties (tensile strength, stiffness, flexibility) and EMI shielding effectiveness of these composites. Furthermore, the role of electron beam (EB) irradiation at 200 kGy in creating cross-linked structures to boost conductivity and shielding performance was thoroughly examined. Fabricated via melt compounding, the composites’ electrical conductivity, and EMI shielding capabilities were the main focus. Results show that the EB-irradiated composite with 30 wt% chemically treated rCF achieved a peak electrical conductivity of 1.34 × 10−8 S/m and an impressive shielding effectiveness of 46.13 dB. These findings offer crucial insights for developing high-performance, cost-efficient, and potentially sustainable rCF-filled ABS composites for advanced EMI shielding applications.